Pengaruh Kemudahan Akses Pembiyaan, Sosialisasi Produk Dan Literasi Nasabah Terhadap Eksistensi Bank Syariah Indonesia (BSI) di Pedesaan - Aydiny Ummy Nurhalim Harahap; Tuti Anggraini (ITB AAS INDONESIA Surakarta, 2023)
This study aims to determine the effect of ease of access to financing, product socialization and customer literacy on the existence of Indonesian Islamic Banks (BSI) in rural areas. This research was conducted in the village of Wonosari, Tanjung Morawa, Deli Serdang. This research is a type of quantitative research using primary data. The sampling technique in this study was to use a saturated sample so that the number of samples in this study was 99 respondents from the total population. The data analysis technique in this study used the SPSS statistical tool. The results of this study indicate that ease of access, product socialization and customer literacy have a positive and significant effect on the existence of a bank. This is shown from the results of the tests carried out. From the research results it is also known that the coefficient of determination is 0.741. This means that 74.1% of bank existence is influenced by ease of access, product socialization and customer literacy, while the remaining 25.9% of bank existence is influenced by other variables not examined in this study.